Inovasi Pembelajaran Pendidikan Agama Islam Dan Budi Pekerti: Pendampingan Penerapan Model TGT Berbasis ABCD Di SMPN 4 Panyabungan - Arif Nasution, Marlian; Riski, Rina (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2025)
Learning in Islamic Religious Education and Character Building (PAI-BP) faces the persistent challenge of dominance by conventional methods (teacher-centered learning), which severely impacts students’ low motivation and active participation. This community service program aims to address this issue through pedagogical innovation by providing intensive assistance in the implementation of the Cooperative Learning Model Type Teams Games Tournament (TGT). The methodology employed is Asset-Based Community Development (ABCD), focusing on the Discovery, Dream, Design, Define, and Destiny stages, specifically oriented toward the empowerment of PAI-BP teachers at SMP Negeri 4 Panyabungan. Implementation results demonstrate that the program successfully transferred TGT technical skills to the partner teachers, evidenced by a significant increase in teacher understanding from 45% to 88% (during the Define stage). Furthermore, the application of TGT (during the Destiny stage) was empirically proven effective in boosting student learning motivation, supported by a 21.5% average increase in motivation questionnaire scores and observations showing high collaboration and participation during tournament sessions. The conclusion of this activity is that the TGT assistance successfully established a new skill asset for the partner teachers, shifted the learning paradigm toward Student-Centered Learning, and ensured the sustainability of innovation that contributes significantly to enhancing the quality of PAI-BP instruction at the school